2022
DOI: 10.1111/jfpe.14098
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and experimental verification of temperature prediction model for quick‐frozen strawberry jetted with dry ice

Abstract: In this study, the quick-freezing model and heat transfer model of quick-freezing of strawberries with dry ice at different flow speeds were proposed to ensure the quality of quick-frozen strawberries and control the jetting amount of dry ice. The aim of this study was to investigate the changes of internal and external temperature in the process of quick-freezing strawberries by jetting dry ice. The quick-freezing experiment platform of strawberries based on dry ice jetting was built for a quick-freezing expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Assuming that the fluid is incompressible, the physical property of the fluid is constant, there is no internal heat source, and the heat dissipation due to viscous dissipation is negligible, the heat exchange process conforms to the third boundary condition [10,11] ; The diced mango sprayed by dry ice particles and the material tray are forced convection heat exchange.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Assuming that the fluid is incompressible, the physical property of the fluid is constant, there is no internal heat source, and the heat dissipation due to viscous dissipation is negligible, the heat exchange process conforms to the third boundary condition [10,11] ; The diced mango sprayed by dry ice particles and the material tray are forced convection heat exchange.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Compressed DI has found applications in many areas. Zhao et al, 2022, indicated that DI blocks were successfully used for the rapid cooling of food products [15]. The article by Dzido et al, 2023, describes numerical studies on the removal of solid deposits on the surface, using the dry ice blasting method, in which external coatings were removed by hitting the surface with DI pellets, which rapidly decompressed while penetrating into gaps between the coating and the substrate [16].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a non-uniform density distribution (DD) in the end products of the carbon dioxide (DI) pellet extrusion process. This, due to the peculiar properties of DI, significantly affects the possibility of its effective use, e.g., in the cooling process [ 11 ]. It results from the unforced phase transition that the material undergoes, i.e., sublimation under normal conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%